Midwifery and Nursing Students’ Emotional Intelligence and Its Relation to Spiritual Intelligence - Arefeh Erfan; Fariba Haghani; Athar Omid; Maryam Baratali (مجله ایرانی آموزش در علوم پزشکی, 2016)
Introduction: Emotional intelligence and spiritual intelligence can be complementary to make life healthy. Emotional intelligence indicates the recognition of one’s own feelings and using them to make the right decisions in life. Spiritual intelligence causes the stability of desirable traits by strengthening spirituality and thus, the individual moves towards growth and perfection. The purpose of this study was to examine the relationship between emotional intelligence and spiritual intelligence in nursing and midwifery students of Isfahan University of Medical Sciences.